Cybersecurity advocates: discovering the characteristics and skills of an emergent role. (22nd March 2021) - Haney, Julie M.; Lutters, Wayne G.
Abstract : Purpose: Cybersecurity advocates safeguard their organizations by promoting security best practices. This paper aims to describe the skills and characteristics of successful advocates. Design/methodology/approach: This study involved 28 in-depth interviews of cybersecurity advocates. Findings: Effective advocates possess not only technical acumen but also interpersonal skills, communication skills context awareness and a customer service orientation. Practical implications: Non-technical skills are deemphasized in cybersecurity training, limiting career progression into the cybersecurity advocate role for existing security professionals and those from other disciplines. This paper suggests improvements for professional development that encourage greater security workforce diversity. Originality/value: To the best of the authors' knowledge, this study is the first to define and enumerate competencies for the role of cybersecurity advocate.